ОСОБЛИВОСТІ ІНТЕЛЕКТУАЛЬНОГО РОЗВИТКУ ТА ФОРМУВАННЯ ЕМОЦІЙНОЇ КУЛЬТУРИ МОЛОДШИХ ШКОЛЯРІВ В УМОВАХ ОСОБИСТІСНО ЗОРІЄНТОВАНОГО ПІДХОДУ ДО НАВЧАННЯ (Pedagogy of Higher and Secondary Education, 2012)
Стаття присвячена вивченню інтелектуальних здібностей та формуванню емоційної культури молодших школярів в умовах особистісно орієнтованого підходу до навчання. Розглядаються мотиваційні аспекти у сукупності інтересів особистості в умовах забезпечення якісно нового процесу навчання.Ключові слова: розвиток інтелекту, розвиток особистості, емоційність процесу навчання, емоційна підготовка учнів.The article is devoted to the studying of intellectual abilities and the forming of younger pupil’s emotional culture under conditions of oriented approach to education. Motivational aspects combined with the person’s interests during high-grade new process of teaching are illuminated in the article. Key words: development of intellect, development of a person, emotionality of the process of teaching, pupil’s emotional preparation.
Keywords: development of intellect; development of a person; emotionality of the process of teaching; pupil’s emotional preparation